PENGEMBANGAN MODUL PEMBELAJARAN BERBASIS LINGKUNGAN DALAM PEMBELAJARAN KIMIA MATERI SISTEM KOLOID - Jaru, Bentino Sanjaya; Tukan, Maria Benedikta; Boelan, Erli Grizca (Jurnal Suluh Pendidikan, 2025)
The purpose of this study was to determine the validity of environment-based learning modules in learning chemistry learning colloidal system material, to determine the learning outcomes of students for knowledge aspects after using environment-based learning modules in learning chemistry learning colloidal system material and to determine the response of students to environment-based learning modules in class XI SMA Negeri 2 Kuwus. The research method used in this research is the development research method (Research & Development) with Sugiyono's development model and is carried out only until the product trial stage. The instruments used in this study were validation, sheets, student learning outcomes sheets and student response questionnaires. The results of this study are the results of material expert validation classified as feasible with an average percentage of 86%, the results of media expert validation classified as feasible with a percentage of 90%, student responses after using the developed environment-based learning module classified as good with a percentage of 91% and student learning outcomes after using the developed environment-based learning module included in the complete category with an average value of 87.